Teacher perceptions of La Nueva Escuela Mexicana: Implementing Gender Equality in Elementary Classrooms - Guel Rodríguez, Juan Manuel (2025)
This study examined the perspectives of in-service primary school teachers on  gender equality as a foundational component of La Nueva Escuela Mexicana (The New Mexican School Reform). Focus groups were held in the 2023–2024 academic year with five female educators from several academic disciplines, all employed at the same urban elementary institution associated with the Benemérita y Centenaria State Teacher Training School in San Luis Potosí, Mexico (Benemérita y Centenaria Escuela Normal del Estado).  The results reveal that teachers view the classroom as a crucial setting for addressing and modifying discriminatory practices. The executed projects fostered student thinking and resulted in noticeable transformations in school life, including a more equitable distribution of resources and communal areas. The study revealed ongoing obstacles, such as cultural opposition from families and students, inaccuracies in textbooks, and insufficient teacher training in implementing a gender perspective when confronting traditional norms and practices in school and family settings.Despite these challenges, the study underscores the transformative potential of integrating gender equality into educational practices, especially when bolstered by robust pedagogical tools and sustained collaboration between schools and communities within a collective, ongoing awareness-building initiative.